Novel viral vector vaccines for tropical infections - Rampling, T (2017)
Plasmodium falciparum (P.falciparum) malaria accounts for over 200 million cases annually and over 400 000 deaths. In 2014 Ebolavirus disease (EVD) caused a devastating outbreak in West Africa, resulting in over 28 000 cases and 11 000 deaths. At present, no licensed vaccine exists for either tropical infection. Viral vectors are showing great promise as a novel vaccine platform technology, having been shown to induce both cellular and humoral immune responses. Malaria vaccine efficacy can be assessed using controlled human malaria infection (CHMI) studies, in which healthy volunteers are infected with P. falciparum and then followed up for development of clinical disease. No such human challenge model exists for EVD. This thesis describes 3 clinical trials. Two studies evaluate the safety, efficacy and immunogenicity of a combination vaccination regimen containing the leading pre- erythrocytic P. falciparum malaria vaccine RTS,S/AS01B and the liver stage, viral vector heterologous prime-boost regimen of ChAd63 ME-TRAP and MVA ME-TRAP. Vaccine efficacy is evaluated using the CHMI model. One trial evaluates a regimen in which immunisation with RTS,S/AS01B and ChAd63/MVA ME-TRAP is chronologically staggered. The other evaluates concomitant administration of the vaccines, and is also the first study to evaluate the effect of a reduced third dose of RTS,S/AS01B when given on a 0, 1, 2-month schedule. The third study presented here is a first in man study describing the safety and immunogenicity of the viral vector Ebolavirus vaccine, ChAd3-EBO Z either given alone or in a heterologous prime-boost sequence with MVA-BN® Filo, for which this study is also a first in man evaluation.